THE EFFECT OF BUDGETARY DECENTRALIZATION (DECENTRALIZATION CUTS) AND THE EFFECTIVENESS OF THE INTERNAL CONTROL SYSTEM ON THE QUALITY OF ACCOUNTABILITY OF THE COOPERATIVE SERVICE'S FINANCIAL REPORTS - Rita J D Atawarman; Natalie Jessica Rubak; Natalia H.Tatuhey; Erika Kili-Kili (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
AThis study aims to empirically test and analyze the influence of Budgetary Decentralization (DP)—including the dynamics of Decentralization Curtailment—and the Effectiveness of the Internal Control System (ICS) on the Quality of Financial Statement Accountability (QFSA) at the Ambon City Cooperatives Office. QFSA is considered a crucial reflection of public entity responsibility, affected by the mechanism of fiscal authority allocation and the internal oversight system. This quantitative research employs a survey method, with the population being all staff involved in the financial cycle at the Ambon City Cooperatives Office (Head of Office, PPK, and PPTK). Given the limited number of relevant subjects, a Saturated Sampling (Census) technique was used. Primary data was collected via a Likert-scale questionnaire and analyzed using Multiple Linear Regression Analysis with SPSS software. Empirically, the results are expected to prove that (1) Budgetary Decentralization (including curtailment dynamics) has a significant influence on QFSA, and (2) The effectiveness of a robust ICS is positively and significantly correlated with QFSA. These findings are important for enriching the public sector accounting literature, highlighting the necessity of balancing delegated authority (decentralization) with the strengthening of internal control to achieve optimal financial statement accountability at the Local Government Unit (SKPD) level